2015
DOI: 10.1242/jeb.088823
|View full text |Cite
|
Sign up to set email alerts
|

Pain in aquatic animals

Abstract: Recent developments in the study of pain in animals have demonstrated the potential for pain perception in a variety of wholly aquatic species such as molluscs, crustaceans and fish. This allows us to gain insight into how the ecological pressures and differential life history of living in a watery medium can yield novel data that inform the comparative physiology and evolution of pain. Nociception is the simple detection of potentially painful stimuli usually accompanied by a reflex withdrawal response, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
107
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(112 citation statements)
references
References 89 publications
0
107
0
5
Order By: Relevance
“…However, other studies with similar measurement methods have found the opposite, with castrated piglets spending more time standing than sham-castrated controls (Taylor et al 2001). Such differing results highlight the difficulty in reliably assessing pain in animals, as a response that is specific to the individual and can be very difficult to compare among individuals (Sneddon and Gentle 2000).…”
Section: Relationships Between Chute Navigation Time and Pen Behaviourmentioning
confidence: 97%
“…However, other studies with similar measurement methods have found the opposite, with castrated piglets spending more time standing than sham-castrated controls (Taylor et al 2001). Such differing results highlight the difficulty in reliably assessing pain in animals, as a response that is specific to the individual and can be very difficult to compare among individuals (Sneddon and Gentle 2000).…”
Section: Relationships Between Chute Navigation Time and Pen Behaviourmentioning
confidence: 97%
“…Pain is a complex and individual sensation, which means that it is difficult to measure and compare among animals (Sneddon and Gentle, 2000) and handling could also interfere with the behavioural and physiological responses of young pigs (Prunier et al, 2005). During the last years, methods to reduce pain with anaesthesia and/or analgesia were investigated (Sutherland et al, 2010;Hansson et al, 2011;Kluivers-Poodt et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the differences in the experimental procedures between the work of Steenbergen and Bardine (2014) and the present study [Steenbergen and Bardine (2014) did not report any settling period prior to treatment with acid and the exposure time to the acid was much lower at 3 min versus 10 min in the present study], their results agree with those of our experiment, which confirms that very low concentrations of acetic acid evoke an increase in the locomotor activity of the fish. This may reflect an escape response from a potentially harmful, noxious stimulus and represents a nociceptive reflex (Sneddon, 2015;Sneddon et al, 2014). The minimum concentration required to elicit a significant change in the locomotor activity of the zebrafish has not been determined yet, as different factors could play a role in the threshold that the nociceptors need to respond to the acid via immersion and different concentrations could have different effects.…”
Section: Experiments 1: Impact Of Noxious Chemicals On Larval Behaviourmentioning
confidence: 99%
“…Appropriate analgesia should be applied to minimize the impact on animals undergoing experimental procedures that cause tissue damage (Sneddon, 2015). In addition, behavioural alterations elicited by any noxious stimulation should be reduced by the use of analgesics or painkillers .…”
Section: Introductionmentioning
confidence: 99%